MODEL PENGUATAN KELEMBAGAAN USAHA MIKRO DAN KECIL UNTUK PENGENTASAN KEMISKINAN - Muzakar Isa; Liana Mangifera; Aflit Nuryulia Praswati; Helmia Khalifa Sina; Agus Wahyudi; Agus Suwondo; Wawan Kurniawan (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Micro and small businesses have an important role in alleviating community poverty at the village level. This study aims to identify the potential and problems of micro and small enterprises, formulate strategies for developing micro and small enterprises, and develop models for strengthening business institutions for poverty alleviation at the village level. This research use desciptive qualitative approach. The research was conducted in Sragen Regency, Central Java Province. Sragen Regency has 51 poor villages, 208 kelurahan/village. This study uses primary data obtained from structured interviews and FGDs. Structural interviews were conducted with micro and small business actors in poor villages to obtain in-depth results. FGDs were conducted with Village Leaders, Community Leaders, District Leaders, and regional organozation regarding the development of micro and small businesses in Sragen Regency. Data analysis used descriptive analysis and content analysis. The results of the analysis show that poor villages in Sragen Regency have various potentials that can be developed as natural tourism villages and pre-employment villages. The strategy for developing micro and small businesses in poor villages can be carried out through increasing the promotion of tourism destinations as well as developing a creative economy and developing tourist area amenitie; increasing the production and marketing of micro and small enterprises; and increased production and productivity of the agricultural and fishery and animal husbandry sectors. The model for developing micro and small businesses in poor villages should be carried out through strong institutional strengthening involving all relevant stakeholders, namely universities, local governments, business actors, associations/societies, and community leaders.